Analisis Pengaruh Kepemimpinan, Pelatihan, dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Pungkook Indonesia One Grobogan - Agustina Putri Utami; Wagiyem (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the effect of leadership, training, and work environment on employee performance at PT Pungkook Indonesia One Grobogan both partially (individually) and simultaneously. The research method uses quantitative descriptive analysis. The population in the study were warehouse employees with questionnaires distributed to 102 respondents. Data analysis techniques used the f test, t test, and multiple linear regression. Based on the results of data analysis in the study, it shows that leadership, training, and work environment have a significant effect on employee performance at PT Pungkook Indonesia One Grobogan. However, partially leadership does not affect employee performance as seen from the t count value (0.523)< t table (1.984) and a sig value of 0.602, so the hypothesis is rejected. Training has a significant effect on employee performance with the results of the t count value (2.374)> t table (1.984) and a sig value of 0.020, and the work environment has a t count (4.562)> t table (1.984) and a sig value of 0.000.